Intramuscular Dirofilariasis Mimicking an Orbital Metastasis in a Patient with Breast Cancer - Brett M. Henderson; Christopher H. Hunt; Laurence J. Eckel; Kara M. Schwartz; Felix E. Diehn; Bobbi S. Pritt; David J. Schembri Wismayer; James A. Garrity (Case Reports in Radiology)
We present the unusual case of a 74 year-old female with a history of breast cancer who presented with acute painless orbital swelling and vertical diplopia. MRI revealed a focal enhancing mass within the superior rectus muscle. As the concern for metastatic disease was high, surgical biopsy was performed and revealed an unusual mimicker of metastatic disease, the parasitic infection dirofilariasis.